Learning with ALeA: Tailored experiences through annotated course material - Kruse, Theresa; Berges, Marc-Pascal; Betzendahl, Jonas; Kohlhase, Michael; Lohr, Dominic; Müller, Dennis (INFORMATIK 2023. Designing Futures: Zukünfte gestalten, 2023)
We present ALeA, an adaptive learning assistant for university courses. The intelligent tutoring system (ITS) provides services for both, learners and instructors, based on semantically annotated course material. The system can generate learning tools like flashcards, guided tours, and quizzes, which can be tailored to individual learning progress. Currently, the system is only available for courses from the field of computer science, like artificial intelligence. We plan to expand it for further courses from different field
Keywords: learning assistant; self-learning; learning analytics; adaptive learning